EFFECTIVE METHODS OF TREATING INTESTINAL DISEASES OF THE STOMACH - Izzatullayeva Dilfuza Ne’matovna; Xodjayeva Naimaxon Umirzaqovna; Turg’unov Zokirjon Alimjonovich (Galaxy International Interdisciplinary Research Journal, 2024)
Intestinal diseases of the stomach, encompassing a wide range of gastrointestinal disorders, require comprehensive medical management to alleviate symptoms and improve the quality of life. This article explores current effective treatment methodologies, supported by clinical research and case studies. We review pharmacological, dietary, and alternative treatment approaches, offering insight into successful management strategies. The findings are intended to guide healthcare practitioners and patients in selecting the best course of action.